Economic Welfare of Village Communities through the Village Fund Management Effectiveness Program - Rosa, Irene Via Dollo; Sopanah, Ana; Bahri, Syamsul (PT. AHS Konsultan dan Pelatihan, 2024)
The purpose of this study is to determine the effectiveness of village fund management on economic welfare, determine the supporting and inhibiting factors of village fund management. The research conducted used qualitative methods. The data used were interviews with 4 informants, namely village heads, secretaries, treasurers and communities in Dedekadu Village, Loli District, West Sumba Regency, and took documentation in the form of Dedekadu Village financial budget reports for the 2022-2023 period. The results of the study proved that the effectiveness of village fund management on the economic welfare of the community in Dedekadu Village, Loli District, West Sumba Regency, namely planning by conducting hamlet deliberations, implementation by making village projects adjusted to budget planning, supervision by conducting internal work evaluations by carrying out Accountability Report activities attended by the community. The form of action to improve the economic welfare of the community is the provision of social assistance to people who cannot afford it in the form of basic necessities and improving roads as access to ease of community mobility. Supporting factors are community participation in voicing voices for village development activities, adequate office equipment, cooperation (coordination) between village officials, village officials have good knowledge and insight in managing village funds. The inhibiting factor is that the village's original income and village fund budget are insufficient to improve village development.